En suivant Matisse... : Collections du Musée de Grenoble. - Carignon, A.; Monery, Jean-Paul (Grenoble : Musée de Peinture et de Sculpture Grenoble, 1984)
Bill, Max ; Bishop, James ; Cruz-Diez, Carlos ; Degottex, Jean ; Debré, Olivier ; Francis, Sam ; Fruhtrunk, Günter ; Kelly, Ellsworth ; LeWitt, Sol ; Monory, Jacques ; Muller-Brittnau, Willy ; Raysse, Martial ; Twombly, Cy ; Wesselman, Tom
En suivant Matisse... : Collections du Musée de Grenoble, Musée de Peinture et de Sculpture Grenoble, 1984
Frans
boek